Study of photorefractive effect in crystals Pb₅Ge₃O₁₁:Cu and Pb₅Ge₃O₁₁ - Gnatovsky, O.; Linnik, V.; Pryadko, L. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
For the first time photorefractive properties of Pb₅Ge₃O₁₁:Cu were studied and compared with those of Pb₅Ge₃O₁₁crystals. Diffraction efficiency of holographic grating registered on Pb₅Ge₃O₁₁:Cu and Pb₅Ge₃O₁₁crystals was 2.5% and 2.2% for λ = 632.8 nm as well as 0.4% and 5.3% for λ = 496.5 nm, respectively. Amplification factor value measured at λ = 632.8 nm was found to be 1.14 cm⁻¹ for Pb₅Ge₃O₁₁ and 2.43 cm⁻¹ for Cu-doped Pb₅Ge₃O₁₁.